The music shop ebook A novel. - Joyce, Rachel (2018)
“An unforgettable story of music, loss and hope. Fans of  High Fidelity,  meet your next quirky love story.”— People NAMED ONE OF THE BEST BOOKS OF THE YEAR BY  THE TIMES  (UK) AND THE WASHINGTON POST It is 1988. On a dead-end street in a run-down suburb there is a music shop that stands small and brightly lit, jam-packed with records of every kind. Like a beacon, the shop attracts the lonely, the sleepless, and the adrift; Frank, the shop’s owner, has a way of connecting his customers with just the piece of music they need. Then, one day, into his shop comes a beautiful young woman, Ilse Brauchmann, who asks Frank to teach her about music. Terrified of real closeness, Frank feels compelled to turn and run, yet he is drawn to this strangely still, mysterious woman with eyes as black as vinyl. But Ilse is not what she seems, and Frank has old wounds that threaten to reopen, as well as a past it seems he will never leave behind. Can a man who is so in tune with other people’s needs be so incapable of connecting with the one person who might save him? The journey that these two quirky, wonderful characters make in order to overcome their emotional baggage speaks to the healing power of music—and love—in this poignant, ultimately joyful work of fiction. Praise for The Music Shop   “Captures the sheer, transformative joy of romance.” — The Washington Post   “Love, friendship, and especially the healing powers of music all rise together into a triumphant crescendo. . . . This lovely novel is as satisfying and enlightening as the music that suffuses its every page.” — The Boston Globe   “Magnificent . . . If you love words, if you love music, if you love love, this [novel] will be without question one of the year’s best.” — BookPage (Top Pick in Fiction)   “Joyce has a knack for quickly sketching characters in a way that makes them stick. [ The Music Shop ] will surprise you.” —Minneapolis Star Tribune “Rachel Joyce has established a reputation for novels that celebrate the dignity and courage of ordinary people and the resilience of the human spirit. . . . But what really elevates The Music Shop is Joyce’s detailed knowledge of—and passion for—music.” — The Guardian